Tense-aspect : between semantics & pragmatics : containing the contributions to a Symposium on Tense and Aspect, held at UCLA, May 1979 - Hopper, Paul J. (Typological studies in language, 1982)
This volume consists of articles based on contributions to a symposium entitled "Tense and Aspect: Between Semantics and Pragmatics" which was held on the U.C.L.A. campus in May, 1979. The participants were linguists, sharing some common assumptions about language in its relationship to communication and cognition. These submissions reflect the traditions of the series it continues: substantive rather than formal linguistics, an interest in language universals of both function and typology, a commitment to a broadly defined data-base drawing from cross-linguistic, diachronic, developmental, and discourse-pragmatic data